Analisis Harga Pokok Penjualan Terhadap Laba Usaha Peternakan Ayam Petelur Reza Ternak Di Desa Pokohrumba Kecamatan Poleang Kabupaten Bombana - Andi Nurul Mutmainnah; La Ode Turi; Nichen .; Bustang . (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Production costs are an importanta factor ini determining business profit ini laying hen farming because proper management of production costs can influence the by thr business owner. This study aims to analyze the cost of goods sold in increasing business profits at the Reza Ternak laying hen farm located in Pokohrumba Village, Poleang District, Bombana Regency. Determining the cost of goods sold is important for business actors because it becomes the basis for determining selling prices and calculating the profit obtained from business activities. This research used a qualitative method with a descriptive approach. The data used in this study consisted of primary and secondary data obtained through observation, intervies, an documentation. The results of the study indicate that the calculation of the cost of goods sold at the Reza Ternak laying hen farm consists of several components including feed costs, labor costs, electricity costs, medicine costs, and other operational costs. An accuraye calculation of the cost of goods sold can help business owners determine the appropriate selling price and increase the profit obtained fro, the laying hen farming business.